The Effectiveness of Mn EDTA (12%) Micronutrient Fertilizer on Agronomic Performance of Sweet Corn (Zea mays saccharata Sturt.) - Erik Mulyana (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2026)
Sweet corn (Zea mays saccharata Sturt.) is an increasingly popular horticultural commodity in Indonesia, attracting both farmers and consumer. This study aims to evaluate the effectiveness of single‑micronutrient fertilizer Mn‑EDTA (12%) in enhancing the growth and yield of sweet corn (Zea mays saccharata Sturt.). The treatments consisted of control, standard NPK, 0.25 NPK, 0.50 NPK, 0.75 NPK, and 1.00 NPK. The experimental findings demonstrated that the application of single‑micronutrient Mn‑EDTA (12%) fertilizer had a highly significant effect on vegetative growth and yield components of sweet corn, with statistically higher values compared with the control treatment. In general, fertilizer dosages equivalent to 0.25–1.00 NPK produced greater plant height, stem diameter, leaf number, ear length, ear diameter, biomass weight, ear weight with husk, ear weight without husk, plot yield, and productivity than the control. The RAE calculation indicated that the fertilizer was effective when applied at dosages equivalent to 0.75 and 1.00 NPK. The highest effectiveness was observed at the 1.00 NPK dosage, with an RAE value of 101%. Notably, the application of Mn‑EDTA (12%) fertilizer at the 1.00 NPK dosage provided significant field effectiveness, as reflected by the RAE value of 101%. This result implies that the use of single‑micronutrient Mn‑EDTA (12%) fertilizer at the 1.00 NPK dosage increased yield by 1.01 times compared with the yield improvement obtained from the reference fertilizer relative to the control treatment.